Technological innovation: dialogical perspective from the view of Joseph Schumpeter (Research, Society and Development, 2020)
This study aims to reflect on the key concept of technological innovation in the field of health and nursing in a dialogical perspective from the perspective of Joseph Schumpeter. It is a descriptive study with a qualitative approach of the theoretical-reflective type, anchored in the concept of innovation proposed by the economist Schumpeter. The reflections on technological innovation are anchored in three categories, namely: “The triad of economic variation: the entrepreneur, innovation and capital”; “Technological innovation and the health field” and “Nursing as a mediator for the realization of technological innovation”. Therefore, it is considered that there should be an appreciation of creative minds that are concerned with developing technologies that improve care with a view to quality of care and that consequently promote improvement in the working conditions of the professionals involved in the care, but without forgetting whether the risks that technological incorporation may result and when not considered may result in possible iatrogenic diseases.